Areas of endemism in the Nearctic: a case study of 1339 species of Miridae (Insecta: Hemiptera) and their plant hosts. (15th July 2016) - Weirauch, Christiane; Seltmann, Katja C.; Schuh, Randall T.; Schwartz, Michael D.; Johnson, Christine; Feist, Mary Ann; Soltis, Pamela S.
Abstract: Areas of endemism are essential first hypotheses in investigating historical biogeography, but there is a surprising paucity of such hypotheses for the Nearctic region. Miridae, the plant bugs, are an excellent taxon to study in this context, because this group combines high species diversity, often small distribution ranges, a history of modern taxonomic revisions, and comprehensive electronic data capture and data cleaning that have resulted in an exceptionally error‐free geospatial data set. Many Miridae are phytophagous and feed on only one or a small number of host plant species. The programs ndm/vndm are here used on plant bug and plant data sets to address two main objectives: (i) identify areas of endemism for plant bugs based on parameters used in a recent study that focused on Nearctic mammals; and (ii) discuss hypotheses on areas of endemism based on plant bug distributions in the context of areas identified by their host plant species. Given the narrow distribution ranges of many species of Miridae, the analytical results allow for tests of the prediction that areas of endemism for Miridae are smaller and more numerous, especially in the Western Nearctic, than are those of their host plants. Analyses of the default plant bug data set resulted in 45 areas of endemism, 35 of them north of Mexico and many located in the Western Nearctic; areas in the Nearctic are more numerous and smaller than those identified by mammals. The host plant data set resulted in ten areas of endemism, and even though the size range of areas is similar between the Miridae and plant data sets, the average area size is smaller in the Miridae data set. These results allow for the conclusion that the Miridae indeed present a valuable model system to investigate areas of endemism in the Nearctic.